Wage effects of education, work experience, skills, migration status and industry in Canada : results from PIAAC - Annen, Silvia [Verfasser] (My University, 2017)
"The following results derive from a project, which aims to analyse the labour market outcomes of migrants in comparison to native born Canadians. Within this project a mixed methods approach is used - including quantitative analyses of the PIAAC data set, as well as qualitative case studies of Canadian enterprises and expert interviews. In doing so, the usability of foreign qualifications and skills in the labour market is evaluated. The theoretical background is formed by human capital theory - reflecting it critically. This paper uses the Canadian PIAAC data 2012 to analyse the impact of the aspects education, work experience, skills, migration status and industry on individual wages. The analyses refer to the Mincerian wage regression model. The results show the positive income effects of educational attainment and work experience as well as the mostly negative effect of migration. Furthermore, the results prove the significant role industry plays regarding the differentiation of wages." (Author's Abstract)
Keywords: P 1.5 Migranten; G 1.3.3.1 Qualifikationsverwertung; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; I 2.3.2 Nordamerika; Migrant; Qualifikationsverwertung; Anerkennung; Chancengleichheit; Arbeitsmarktchance; Einkommenseffekte; Kanada